Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di Madrasah Aliyah Negeri 1 Kota Sukabumi (International Forum of Researchers and Lecturers, 2024)
This research aims to identify and analyze the leadership style of school principals in improving teacher performance in MAN 1 Sukabumi City. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, observation and document analysis. Research participants consisted of school principals, teachers and administrative staff. The research results show that the transformational leadership style applied by school principals plays a significant role in increasing teacher motivation, involvement and performance. The principal also uses a participative leadership approach by involving teachers in decision making, which has a positive impact on teachers' sense of ownership and responsibility for their duties. In addition, the emotional and professional support provided by the principal creates a conducive and collaborative work environment. The conclusion of this research confirms that the principal's effective leadership style is a key factor in improving teacher performance, which in turn has a positive impact on the quality of education at MAN 1 Sukabumi City.